Extreme weather and natural disasters - Healey, Justin (Issues in society (Balmain, N.S.W.) ;, 2012)
Australia is a vast land in which weather varies significantly in different parts of the continent. Recent extreme weather events in Australia, such as the Queensland floods and Victorian bushfires, are brutal reminders of nature's devastating power. Is global warming increasing the rate of natural disasters? What part do La Niña and El Niño play in the extreme weather cycle? Cyclones, floods, severe storms, bushfires, landslides, earthquakes, tsunamis - what are the natural and man-made causes of these phenomena, how predictable are they, and how prepared are we for the impacts of natural dis.